Global Terrorism Database Analysis - Laycock, Angela; Helliker, Aimee; Critchley, Richard; Hazael, Rachael (Cranfield University, 2025)
Exploring the blast and fragmentation impact design considerations of low carbon construction materials subject to terrorist threats. The dataset is from the Global Terrorism Database with the addition of details around the charge size to enable analysis of trends.
Keywords: Terrorism; explosive; blast; IED